Differences of active substances in different fruit phenotypes of Lycium ruthenicum Murr. - SHI Cui; KONG Dongsheng; WU Yao; BAO Jingwei (Xibei zhiwu xuebao)
[Objective] The aim was to understand the phenotypic variation of Lycium ruthenicum Murr. fruits and the correlation between phenotype and active substances, to provide reference for its resource development and utilization. [Methods] Taking L. ruthenicum as materials, 23 phenotypic characteristics were extracted, and the active substances were determined and analyzed. [Results] (1) The coefficient of variation of roundness, correlation value and entropy of phenotypic characteristics was small, the difference between individuals was small, and the stability was high. The coefficient of variation of area, yellow-blue channel value, red-green channel value, contrast and angular second moment value was large. (2) The coefficient of variation of active substance content was large, the stability was poor, and the selection potential was large. The correlation coefficients between phenotypic characteristics and active substances were extremely significant in 143 pairs (P <0.01) and significant in 20 pairs (P <0.05). (3) Principal component analysis showed that the characteristic vector values of red, green, blue, brightness, lightness, gray, perimeter, area, length, width, angular distance, and energy value were higher, which could be used as important reference factors for fruit quality evaluation. [Conclusion] The fruits of L. ruthenicum have great potential for selection, and the content of active substances can be judged by phenotypic characteristics. These results provide reference for fruit quality evaluation and non-destructive testing.